Indonesian Cultural Diplomacy Strategy Through The Bipa Program In Building An Ecosystem Of Indonesian Language Learners In Germany - Keisha Izzati Marensya; Nurmasari Situmeang (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2026)
As part of Indonesia’s cultural diplomacy and language internationalization agenda, the Indonesian Language for Foreign Speakers Program, known as BIPA, has become an important instrument for promoting Indonesian language and culture abroad. This study examines how the BIPA Program functions as a strategy of Indonesian cultural diplomacy in building an ecosystem of Indonesian language learners in Germany during the 2023–2025 period. Using a qualitative descriptive approach, this study draws on policy documents, relevant literature, institutional reports, and interviews with stakeholders involved in BIPA implementation. The findings show that the BIPA Program in Germany is supported by a strong legal and policy foundation, particularly Law No. 24 of 2009 and related regulations on the internationalization of the Indonesian language. The implementation of BIPA in Germany is carried out through cooperation between Indonesian government institutions, diplomatic representatives, APPBIPA, and German higher education institutions. The study identifies three main strategies: connection, consistency, and innovation. The connection strategy is reflected in institutional networks and diplomatic cooperation; consistency is shown through curriculum development, teacher training, and sustainable program implementation; while innovation appears in the use of digital media, culturally contextualized materials, and interactive learning methods. However, the program still faces several challenges, including limited authentic language environments, bureaucratic constraints, unequal institutional support, and competition with other global languages. The study concludes that BIPA has significant potential to strengthen Indonesia’s soft power in Germany, but its sustainability requires stronger policy coordination, broader promotion, improved teacher capacity, and more adaptive learning innovation.